2022
DOI: 10.1097/md.0000000000031933
|View full text |Cite
|
Sign up to set email alerts
|

Partial sleep restriction-induced changes in stress, quality of life, and lipid metabolism in relation to cold hypersensitivity: A before-and-after intervention study

Abstract: Sleep disturbances are associated with cold hypersensitivity (CH) and characterized by excessive cold sensation in specific body parts and cold thermal discomfort. This study investigated the effects of short-term sleep restriction followed by a recovery phase on subjective health status, inflammation, and lipid metabolism in different types of CH. A total of 118 healthy adults aged 35 to 44 years without sleep disturbances were enrolled. Participants underwent 4-hour sleep restrictions per day for 3 days at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…These women underwent MYCODE genetic testing prior to enrollment. Our study found a cold hypersensitivity prevalence of 53.92%, consistent with other studies reporting 47.78% to 65.68% cold hypersensitivity prevalence in East Asian populations 6 , 8 , 9 , 15 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These women underwent MYCODE genetic testing prior to enrollment. Our study found a cold hypersensitivity prevalence of 53.92%, consistent with other studies reporting 47.78% to 65.68% cold hypersensitivity prevalence in East Asian populations 6 , 8 , 9 , 15 .…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, cold hypersensitivity can cause distress and hinder the execution of routine activities 6 . In Japan, women with cold hypersensitivity report a painful cold sensation and associated symptoms such as insomnia, fatigue, and edema 7 .…”
Section: Introductionmentioning
confidence: 99%